2023
DOI: 10.1109/tie.2022.3172748
|View full text |Cite
|
Sign up to set email alerts
|

On the Application of Extended Grounded Slot Electrodes to Reduce Noncirculating Bearing Currents

Abstract: Power-electronic-converter-induced motor bearing currents are a widespread problem in the field of electrical drives. Parasitic capacitances between the electrical machine's parts provide a path for leakage currents, which finally harm metallic ball bearings. Remembering that end-windings have a significant contribution in building up stray capacitances, a countermeasure affecting both the lamination stack and end winding areas is needed. This paper focuses on a countermeasure against the non-circulating beari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Many researchers have observed that an electric field between the inner and outer rings can lead to electrical erosion of the bearing surfaces [1]. Electrical damage to bearings has become a critical problem that affects the safe operation of electric motor systems [2][3][4]. Therefore, the mechanism of the electrical erosion of bearings has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have observed that an electric field between the inner and outer rings can lead to electrical erosion of the bearing surfaces [1]. Electrical damage to bearings has become a critical problem that affects the safe operation of electric motor systems [2][3][4]. Therefore, the mechanism of the electrical erosion of bearings has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…For the same target, Vostrov et. all suggested an extended ground electrodes to mitigate their circulation [15]. Alternatively, authors in [16] analysed the Daniele De Gaetano, Wenjun Zhu, Xiangyu Sun, Xiao Chen, Antonio Griffo and Geraint W Jewell are within the Department of Electronic and Electrical Engineering, The University of Sheffield, Sheffield, U.K..…”
Section: Introductionmentioning
confidence: 99%
“…This proportion is gradually increasing with the higher levels of power semiconductor devices and switching frequency [3]. Several factors can contribute to bearing failure, but the most significant one is bearing voltage [4][5][6]. The reason is the highfrequency common mode voltage produced by pulse-width modulation converter.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that, the maintenance costs are high. Electrostatic shielding by electrodes in slots is studied and the results indicate bearing voltage is mitigated effectively [5]. However, the method is suspected to be used in practical engineering.…”
Section: Introductionmentioning
confidence: 99%